Characteristics of gestational thropoblast tumor in Dr. Soetomo Hospital, year 2015-2017 - Yoan A Angelina; Poedjo Hartono (Universitas Airlangga, 2019)
Objectives: To report the characteristics of the patients of Gestational Trophoblastic Neoplasia (GTN) and its management at Dr. Soetomo Hospital, Surabaya, Indonesia. Case Report: There were 41 cases GTN at dr. Soetomo hospital within 3 years, data were collected from January 2015 to December 2017, which are 11 cases develop drug resistance. Conclusion: GTN is a chemosensitive neoplasia but can also experience resistance to chemotherapy. It is important to monitor the levels of beta-HCG for at least 12 months before the patient can get pregnant again.